2013
DOI: 10.1534/genetics.113.154393
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ephrin Receptor Protein Kinase-Independent Signaling in Amphid Axon Guidance in Caenorhabditis elegans

Abstract: Eph receptors and their ephrin ligands are key conserved regulators of axon guidance and can function in a variety of signaling modes. Here we analyze the genetic and cellular requirements for Eph signaling in a Caenorhabditis elegans axon guidance choice point, the ventral guidance of axons in the amphid commissure. The C. elegans Eph receptor EFN-1 has both kinase-dependent and kinase-independent roles in amphid ventral guidance. Of the four C. elegans ephrins, we find that only EFN-1 has a major role in amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…Interestingly, we observed that the VNC defects in dpy-18 mutant animals have a strong left-right bias where left axons cross over to the right fascicle. This leftright bias in neuronal patterning has also been reported recently where loss of Eph signaling causes asymmetric defects in amphid neuron guidance (Grossman et al, 2013). Such findings suggest the asymmetric expression of particular guidance cues and postulate a role for DPY-18 in their localization.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, we observed that the VNC defects in dpy-18 mutant animals have a strong left-right bias where left axons cross over to the right fascicle. This leftright bias in neuronal patterning has also been reported recently where loss of Eph signaling causes asymmetric defects in amphid neuron guidance (Grossman et al, 2013). Such findings suggest the asymmetric expression of particular guidance cues and postulate a role for DPY-18 in their localization.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, we tested whether HSN axon guidance is affected in emb-9 and let-2 mutants. As emb-9 and let-2 mutants are lethal, we used the temperature-sensitive alleles emb-9(hc70) and let-2(b246) for this analysis (Guo et al, 1991;Sibley et al, 1994). Both alleles exhibit embryonic lethality at 25°C, whereas at 20°C they are able to grow.…”
Section: Dpy-18 Acts In Multiple Tissues To Regulate Axon Guidancementioning
confidence: 99%
“…efn-2, efn-3, and efn-4 also act redundantly in PLM extension (Mohamed and Chin-Sang 2006). EFN-1 functions to guide amphid axons ventrally through the amphid commissure Grossman et al 2013); amphid axon ventral guidance also involves partly redundant SAX-3 and netrin signals. EFN-4 also signals via noncanonical mechanisms that do not involve VAB-1 (Chin-Sang et al 2002), and interacts with the L1CAM LAD-2 to provide a cue for the dorsal migration of the SDQ axons (Dong et al 2016).…”
Section: Receptors and Adhesion Moleculesmentioning
confidence: 99%
“…Previous work has identified multiple roles for the C. elegans Eph receptor VAB-1 during development, including embryonic morphogenesis, oocyte maturation, and amphid neuron axon guidance (George et al 1998;Miller et al 2003;Mohamed and Chin-Sang 2006;Ikegami et al 2012;Grossman et al 2013). VAB-1 can bind EFN-4 in vitro, making it an obvious candidate receptor (Wang et al 1999).…”
Section: Efn-4 Promotes Axon Outgrowth 643mentioning
confidence: 99%